Therapeutic recreation-nursing team: a therapeutic intervention for nursing home residents with dementia. - Buettner LL; Ferrario J (Annual in Therapeutic Recreation)
Sixty-six nursing home residents with dementia were selected for participation in this 30- week study. Residents were randomly assigned to the experimental or control group. Baseline testing on cognitive status, depression, agitation, strength, flexibility, and timed 50' walk was completed on all participants, with retesting every 10 weeks during the intervention. The experimental group received a specially designed interdisciplinary program based on level of functioning that flowed into the routine of care. The control group received traditional nursing home activities and care. The repeated measures analysis showed that there was significant improvement of cognitive status, depression, strength, flexibility, and walking for the experimental group. The control group showed significant decline on all of the variables. The results of this study indicate that this type of highly structured interdisciplinary programming may compress morbidity of older adults in the later stages of dementia.